Sistema electrónico para el correcto ensamble de conectores y sistema de visión artificial, para el reconocimiento de fallas en el patrón de color de los cables en conectores discretos. - Sáenz-Fernández, Isaac (Instituto Tecnológico de Costa Rica, 2017)
Cables and connectors represent the fundamental base of electronic systems without them most of the devices used daily as cell phones, tablet computers among many others, would not work. For example, if there are flaws in some inner wires of conventional cell phone use, said movable stop functioning immediately following the affected person would be in a state of confinement to replace or repair the device. For this reason, in building quality cables and connectors it is essential and one of the most important features in production. SAMTEC company reaches Costa Rica in 2006, since then produces over 1,000 different products used in cars as well as airplanes computers at NASA and the US Army. Quality, hand in hand with performance verification systems and extensive testing 100% of production guarantee products of high demand for efficiency and effectiveness. Being one of the goals SAMTEC the keep pace with technological growth and meet the expectations of the demanding labor market, it proposes the development of a project, which aims to eliminate production errors in connectors have cable color, which they have a color pattern set by the client and that order should not be altered. These connectors are of SFSD of SAMTEC series and assembled manually by an operator inserting each wire individually so that human error is the basis of the problem. To achieve eliminate production problems two stages were developed, the first one assisted assembly system for the operator, where using a visual aid, it shows the position and color of the cable to be inserted once the cable set, it indicates the position and color of the next cable. The second stage is a final check of the finished connector, where by a camera and Vision Builder National Instruments software, verified that all cables are in the position that corresponds as color pattern, otherwise, the system indicates that an error exists in the connector.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2017.
Keywords: Cables; Conectores; SAMTEC; Vision Builder NI; Identificador de color